Emblematics in Antonio Machado’s poetry - De Ros, X (Routledge, 2018)
The pictorial quality of many of Antonio Machado’s poems has been the object of extensive critical attention, and this quality reveals a perceptive eye for the visual image as well as a knowledge of the principles of composition and execution in contemporary painting. This was an interest fostered by his education at the Institución Libre de Enseñanza (ILE) and by his frequent visits to El Prado. At the same time his fondness for the aphoristic genre became increasingly manifest in his poetry and his prose, as discussed by James Whiston and other critics. This essay explores the presence in his work of these two characteristics or interests which are combined in the art of the emblem, and examines several instances of ‘emblematic’ poems in his work. In these poems the poetics of that tradition are conjured up in the visual nature of their central images. The analysis leads to some unexpected encounters with Shelley and Baudelaire.